Resource frontiers and agglomeration economies: The varied logics of transnational land-based investing in Southern and Eastern Africa - Dilini Abeygunawardane; Angela Kronenburg García; Zhanli Sun; Daniel Müller; Almeida Sitoe; Patrick Meyfroidt (Ambio, 2022)
Actor-level data on large-scale commercial agriculture in Sub-Saharan Africa are scarce. The peculiar choice of transnational investing in African land has, therefore, been subject to conjecture. Addressing this gap, we reconstructed the underlying logics of investment location choices in a Bayesian network, using firm- and actor-level interview and spatial data from 37 transnational agriculture and forestry investments across 121 sites in Mozambique, Zambia, Tanzania, and Ethiopia. We distinguish four investment locations across gradients of resource frontiers and agglomeration economies to derive the preferred locations of different investors with varied skillsets and market reach (i.e., track record). In contrast to newcomers, investors with extensive track records are more likely to expand the land use frontier, but they are also likely to survive the high transaction costs of the pre-commercial frontier. We highlight key comparative advantages of Southern and Eastern African frontiers and map the most probable categories of investment locations.
Keywords: 330; agricultural investments; Bayesian belief network; decision model; deforestation; large-scale land acquisition; land use change